Implementasi Pemberdayaan Keluarga dalam Mencegah Kegawatdaruratan Stroke dengan Metode Face, Arms, Speech, Time (Fast) - Andrianur, Frana; Supriadi B., Supriadi B.; Parellangi, Andi; Rahman, Gajali; Setiadi, Rizky (Poltekita: Jurnal Pengabdian Masyarakat, 2025)
Stroke continues to increase which is a burden globally, the main prevention strategies are currently implemented but are not effective enough, so new prevention strategies will need which are expected to have a greater effect. Rapid recognition and reaction to signs of stroke and TIA is the concept of "Time is brain" which means treatment of stroke which is an emergency. Community dedication aimed to make families able to use the Face, Arm, Speech, Time (FAST) method which is emergency anticipation of the risk of stroke. The method of empowering families through family assistance in carrying out health checks and counseling activities. The target of the activity is 30 people in PKM Bengkuring Samarinda. We have results obtained by the community dedication are differences in knowledge scores before and after showing (p = 0.001). increased knowledge before (med 60 ± min 30 - max 80) and after training (med 90 ± min 70 - max 100). This family empowerment intervention in face, arm, talk, time (FAST) detection method has been proven to increase knowledge to prevent stroke. To prevent stroke emergencies, we must be alert when they occur and need fast medical treatment both at home, office and at school.